PROFESSOR SIDNEI QUEZADA: O ENGENHEIRO DA EDUCAÇÃO EM CIÊNCIAS (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
With the objective of paying homage to Professor Sidnei Quezada Meireles Leite, this text describes a brief memory of his life, contemplating the account of his childhood and his dedication to studies, going through his professional and academic achievements, especially at Fundação Osvaldo Cruz and Federal University of Rio de Janeiro and his coming to the Federal Institute of Espírito Santo, in addition to the accomplishment of his Post-doctoral internships in Education by the National University of Brasília and by the University of Aveiro - Portugal. It is characterized as a biographical narrative based on an interview with one of his sisters, with consultations on documents, descriptions of messages sent via cell phone applications, e-mail or social network and the authors' recollection at times experienced with him. As a result, it is considered a way to perpetuate the legacy of teachers of education, colleagues, students and alumni as a science education engineer.
Keywords: Sidnei Quezada Meireles Leite, Science Education, Federal Institute of Espírito Santo.